Virtual Turbocharger as a Tool for Reality Simulation - Novotný, Pavel; Vacula, Jiří; Kudláček, Petr (Springer, 2021)
The mobility of people and the transport of goods requires powertrains. These powertrains often include internal combustion engines with turbocharging technology. The development of turbochargers requires an increase in their efficiency, for example in the form of reduced mechanical losses. In parallel, however, related processes such as vibration, gas blow-by through the sealing system or lubricant consumption still need to be addressed. The virtual turbocharger is a multiphysical tool for the coupled solution of these processes. This physically wide model is described by a system of differential and algebraic equations, assembled in a multibody system, discretized and solved numerically. The solution results are suitable for calibration by experiments on real turbocharger. A reasonably good agreement with experiments is achieved using the example of a truck engine turbocharger. In terms of the physical description of the processes, the development of computational modelling will continue to proceed simultaneously in two different directions. On the one hand by trying to increase the depth of the physical description, on the other hand by including more physical problems within a single virtual prototype.

The mobility of people and the transport of goods requires powertrains. These powertrains often include internal combustion engines with turbocharging technology. The development of turbochargers requires an increase in their efficiency, for example in the form of reduced mechanical losses. In parallel, however, related processes such as vibration, gas blow-by through the sealing system or lubricant consumption still need to be addressed. The virtual turbocharger is a multiphysical tool for the coupled solution of these processes. This physically wide model is described by a system of differential and algebraic equations, assembled in a multibody system, discretized and solved numerically. The solution results are suitable for calibration by experiments on real turbocharger. A reasonably good agreement with experiments is achieved using the example of a truck engine turbocharger. In terms of the physical description of the processes, the development of computational modelling will continue to proceed simultaneously in two different directions. On the one hand by trying to increase the depth of the physical description, on the other hand by including more physical problems within a single virtual prototype.
Virtual Turbocharger as a Tool for Reality Simulation
Keywords: Virtual turbocharger Turbocharger Bearing Gas blow-by Vibration Efficiency; Virtual turbocharger Turbocharger Bearing Gas blow-by Vibration Efficiency